Optimizing The Role Of School Public Relations In Addressing Hate Speech And Building A Positive Image - Muthi’ah Rahman; Unzilah Khomairohtusshiyamah; Uryatul Hikmah; Najiburrahman; Hasan Baharun (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
In educational institutions, especially in schools, it is very interesting to observe the effectiveness of school community communication when facing hate speech issues and increasing positive synergy in implementing communication strategies. Nowadays, technology has developed very rapidly, making it very easy for negative and positive narratives to spread widely through communication, especially the use of social media. In this observation, the researcher used a qualitative method with a case study approach, collecting data from all elements within the school environment. In the educational context, it is certainly crucial to understand the patterns, programs, and follow-up in the implementation of communication management, so that the collected data can be analyzed in depth. It can be concluded that in communication relationships, all elements of the school community, especially policymakers, can significantly influence the process of disseminating negative and positive information on a massive and sustainable basis. Therefore, it is important to emphasize when stakeholders organize training activities on social media content and digital literacy, and also not forgetting parents, as part of the school community, because it is proven to increase the effectiveness in preventing negative narratives from circulating very quickly. Ultimately, every school must have a guideline to address the challenges facing the school environment by embracing all aspects, thereby addressing the prevention of hate speech and safeguarding the reputation of an educational institution.